PENYELENGGARAAN PENDIDIKAN INKLUSIF PADA MADRASAH IBTIDAIYAH (MI) KEJI UNGARAN JAWA TENGAH: THE IMPLEMENTATION OF THEINCLUSIVE EDUCATION AT ISLAMIC ELEMENTARY SCHOOL (MI) KEJI UNGGARAN IN CENTRAL JAVA - Umi Muzayanah (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
The aim of this research was to describe the implementation of the inclusive education at Islamic Elementary School (MI) Keji Unggaran in Central Java. This research used the qulitative approach. The results of research showed that the implementation of the inclusive education at MI Keji run well although it was in its restrictiveness. The learning process was conducted with pull out system where the curriculum would be used were modified from the national curriculum, the madrasah curriculum, and the individual education program (PPI) curriculum. The teachers’ existence asthe students’ advisor which were not relevant with their background education did not decrease their spirit to serve the the equal education for their disabled students. Keywords: Inclusive education, madrasah, disabled students, Semarang Melalui pendekatan kualitatif, penelitian ini bertujuan untuk mendeskripsikan pelaksanaan program inklusif di MI Keji Ungaran Jawa Tengah. Hasil penelitian menunjukkan, bahwa penyelenggaraan program inklsuif di MI Keji berjalan dengan baik di tengah keterbatasan yang dimiliki. Proses pembelajaran dilakukan dengan sistem pull out, di mana kurikulum yang digunakan merupakan modifikasi dari kurikulum nasional, kurikulum madrasah, dan Kurikulum Program Pendidikan Individual (PPI). Keberadaan guru pembimbing dengan latar belakang pendidikan yang kurang relevan tidak menyurutkan semangat mereka untuk memberikan pendidikan yang setara bagi anak berkebutuhan khusus. Kata Kunci: Pendidikan inklusif, madrasah, Anak Berkebutuhan Khusus, Semarang